~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

Multiplying the brackets:

#3(x-2)# is really 3 off # (x-2)#

That is #(x-2) + (x-2)+(x-2)#

So we end up with #x+x+x -2-2-2#

Which is 3 of #x# written as #3x# and we also have 3 lots of #-2# which is #-6#

So# 3(x-2) =3x-6#

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

So the original equation of

#color(white)(xxxxxxx)color(brown)(-4=-8+3(x-2))#

Becomes

#color(white)(xxxxxxx)-4=-8 +3x-6#

#color(white)(xxxxxxx)-4=3x-14#

Add #color(blue)(14)# to both sides

#color(white)(xxxxxxx)color(brown)(-4) color(blue)(+14) color(brown)(=3x-14)color(blue)(+14)#

#color(white)(xxxxxxxxxxxxxx)10=3x#

Divide both sides by 3

#color(white)(xxxxxxxxxxxxxx)10/3 = 3/3 x#

#color(white)(xxxxxxxxxxxxxx)10/3 =x#

Write as per convention

#color(white)(xxxxxxxxxxxxxxxx)color(green)(x=10/3)#